Metal-hybridized magnetic nano-chitosan and application thereof
Through the preparation of metal hybrid magnetic nanochitosan nanoparticles, the preparation complexity and sustainability of existing magnetic nanoparticles in DNA separation are solved, efficient DNA separation is achieved, and adsorption capacity and material performance are improved.
Patent Information
- Application Number
- CN202411550013.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
AI Technical Summary
The existing magnetic nanoparticles are made in complex process, poor sustainability, small load, low efficiency, high price during DNA separation, and have safety and pollution problems.
Using metal hybrid magnetic nanochitosan nanoparticles, it is modified by magnetic iron tetraoxide nanoparticles, covered with silica and sodium dodecyl sulfate, and then wrapped chitosan and doped with metal ions to prepare high-quality DNA adsorption performance nanoparticles.
It realizes rapid and high-throughput separation of DNA, simplifies the preparation steps, improves the specific surface area and active adsorption sites of the material, significantly improves the DNA capture ability, and has wide application value.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biochemistry, in particular to metal hybridized magnetic nano-chitosan and application thereof. Background Art
[0002] Deoxyribonucleic acid (DNA) is the most important carrier of genetic information in biological cells. DNA carries the genetic information necessary for the synthesis of RNA and proteins, and is an essential biological macromolecule for the development and normal functioning of organisms. Gene therapy, animal and plant pathogen detection, human disease diagnosis and DNA tracing are all inseparable from the DNA separation process. Therefore, high-quality and efficient DNA extraction is crucial to the development of many molecular biology, genetics, and modern biomedicine.
[0003] There are many methods to isolate DNA, and these techniques are usually divided into two types: solid phase and liquid phase. Liquid phase extraction techniques contain a mixture of chloroform / phenol and hexadecyltrimethylammonium bromide, and usually require complex stages such as precipitation, centrifugation and filtration. In addition, this treatment method is laborious, toxic and time-consuming. Traditional solvent techniques commonly used for DNA isolation still consume a large amount of toxic organic solvents and require repeated centrifugation steps or the use of animal-derived enzymes. This complex process inevitably increases time and economic costs. Compared with traditional methods, solid phase extraction has become a more suitable choice to reduce or avoid the use of organic solvents and is environmentally friendly. Several nanocomposites have been developed for DNA extraction, including polymer ionic liquids, graphene oxide, chitosan, silica gel and cellulose. However, this method still involves solid-liquid phase extraction and requires repeated time-consuming centrifugation steps.
[0004] As an upgraded version of solid phase extraction, magnetic solid phase extraction technology is becoming increasingly popular in genomic DNA separation, because magnetic particles are easily attracted by external magnetic fields during DNA separation, eliminating the need for centrifugation steps and saving time. Therefore, alternative separation processes using various solid phase supports (such as carbon nanotubes, glass fibers, magnetic nanoparticles, metal organic frameworks, and silica) have been proposed. The latest progress in the development of system integration for DNA separation is the use of solid phase supports, among which magnetic nanoparticles have received the most attention due to their ease of handling and cost savings, but the existing preparation process of magnetic nanoparticles is complex, has poor sustainability, small loading capacity, low efficiency, high price, and safety and pollution issues. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide metal hybridized magnetic nano-chitosan and application thereof.
[0006] The invention provides metal hybridized magnetic nano chitosan nano particles, which comprise magnetic ferrosirconium tetroxide nano particles, silicon dioxide, sodium dodecyl sulfate, chitosan and metal ions.
[0007] Specifically, the metal hybridized magnetic nano-chitosan nanoparticles include:
[0008] Magnetic Fe3O4 nanoparticles;
[0009] Silicon dioxide covering the magnetic ferroferric oxide nanoparticles;
[0010] Sodium lauryl sulfate coated on the silicon dioxide;
[0011] Chitosan coated on the sodium dodecyl sulfate;
[0012] and metal ions doped in the chitosan;
[0013] In the present invention, the chitosan includes chitosan with a deacetylation degree of more than 95% and / or a deacetylation degree of less than 95%; in a specific embodiment of the present invention, the chitosan has a deacetylation degree of more than 95%; the molecular weight of the chitosan varies according to the degree of polymerization, and in the present invention, the molecular weight of the chitosan is 40,000 to 80,000, and specifically 50,000;
[0014] The metal ion is selected from at least one of lanthanum, cerium, zirconium and / or aluminum ions. Specifically, the effect is best when the metal ion is lanthanum.
[0015] The particle size of the metal hybrid magnetic nano-chitosan nanoparticles is 60-140 nm, further 80-120 nm, and about 100 nm in the present invention.
[0016] The present invention provides a method for preparing the metal hybridized magnetic nano-chitosan nanoparticles, which comprises the following steps:
[0017] Step 1, the magnetic ferroferric oxide nanoparticles are modified by silica to obtain silica-modified magnetic ferroferric oxide nanoparticles, and the silica-modified magnetic ferroferric oxide nanoparticles are activated by sodium dodecyl sulfate to obtain activated silica-modified magnetic nanoparticles;
[0018] Step 2, the activated silica modified magnetic nanoparticles are coated with chitosan to obtain magnetic nano-chitosan;
[0019] Step 3: The magnetic nano-chitosan is hybridized with metal ions to obtain the metal-hybridized magnetic nano-chitosan nanoparticles.
[0020] The magnetic ferroferric oxide nanoparticles are prepared by reacting trivalent iron ions and divalent iron ions with sodium hydroxide;
[0021] Further, the sources of the ferric ions and the ferrous ions are metal salt compounds carrying the ions, respectively, and the present invention does not limit this; in the present invention, the ferrous ion metal salt is selected from at least one of ferrous sulfate and ferrous chloride; the ferric ion metal salt is selected from at least one of ferrous chloride and ferric ammonium sulfate; in a specific embodiment of the present invention, they are ferrous sulfate and ferric chloride, respectively; in the present invention, the reaction of ferrous sulfate, ferric chloride and sodium hydroxide obtains magnetic ferric oxide nanoparticles; the molar ratio of ferrous sulfate, ferric chloride and sodium hydroxide is 1:3:(30~50); further 1:3:(35~45); in a specific embodiment of the present invention, it is 1:3:40. In a specific embodiment of the present invention, 0.01 mol ferrous sulfate and 0.03 mol ferric chloride are dissolved in 50 mL of water, and then reacted with 100 mL 4 M preheated sodium hydroxide solution to obtain the magnetic ferric oxide nanoparticles.
[0022] The reaction conditions are 60-65°C, 400-800 rpm, 1.5 h;
[0023] After the reaction, the steps of magnetic separation, washing and freeze drying are also included, which are conventional techniques adopted by those skilled in the art and will not be described in detail in the present invention;
[0024] In the present invention, the silicon dioxide ions are obtained by reacting tetraethyl orthosilicate with ammonia water; the silicon dioxide ions obtained by reacting tetraethyl orthosilicate with ammonia water are modified on the surface of magnetic ferrosoferric oxide nanoparticles; in the present invention, magnetic ferrosoferric oxide nanoparticles, ammonia water and tetraethyl orthosilicate are mixed to obtain magnetic ferrosoferric oxide nanoparticles modified with silicon dioxide ions; in a specific embodiment of the present invention, 1 g of the magnetic ferrosoferric oxide nanoparticles is ultrasonicated in 80 mL of anhydrous ethanol, and then reacted with 16 mL of water, 2 mL of ammonia water and 2 mL of tetraethyl orthosilicate at room temperature for 12 h; the reaction conditions are room temperature and stirring for 12 h to obtain the magnetic ferrosoferric oxide nanoparticles modified with silicon dioxide ions.
[0025] The silicon dioxide ion-modified magnetic ferroferric oxide nanoparticles are activated to obtain activated silicon dioxide-modified magnetic nanoparticles;
[0026] The silicon dioxide modification and activation also include steps of cleaning and magnetic separation, which will not be described in detail in the present invention;
[0027] The activation reagent is SDS (sodium dodecyl sulfate), and the activation is performed in the presence of sodium chloride. The mass ratio of the silica-modified magnetic nanoparticles, sodium chloride and sodium dodecyl sulfate is 1:2.9:(0.5~1.2); further 1:2.9:(0.6~0.9); specifically 1:2.9:0.72; in a specific embodiment of the present invention, the silica-modified magnetic nanoparticles are dispersed in 100 mL of water, and 2.9 g of sodium chloride and 0.72 g of SDS (sodium dodecyl sulfate, molecular weight 288.38, about 2.5 mmoL) are added for activation; the activation conditions are: stirring at room temperature for 4 h; the activation also includes the steps of magnetic separation, washing and vacuum drying, which are not described in detail in the present invention;
[0028] In step 2 of the preparation method of the present invention, the mass ratio of activated silica-modified magnetic nanoparticles to chitosan is 1:(0.5-2), further 1:(1-2); specifically 1:1; the chitosan has a deacetylation degree of>95% and a molecular weight of 50,000;
[0029] In step 3 of the preparation method of the present invention,
[0030] The mass ratio of the magnetic nano-chitosan to the metal salt containing the metal ion is 1:(0.5-2); specifically 1:1.4;
[0031] The hybridization is hybridization of magnetic nano-chitosan and metal ions in the presence of sodium hydroxide to obtain the metal-hybridized magnetic nano-chitosan nanoparticles;
[0032] The hybridization temperature is 50°C to 80°C; further 50°C to 70°C; specifically preferably 60°C.
[0033] The magnetic nano-chitosan and the metal ions need to react before hydrogen hybridization; the reaction conditions are ultrasound for 15 minutes and stirring at room temperature for 2 hours.
[0034] The hybridization further includes the steps of magnetic separation, cleaning and vacuum drying, which will not be elaborated in the present invention.
[0035] The present invention prepares metal hybridized magnetic nano-chitosan for nucleic acid extraction. In a specific embodiment of the present invention, the raw materials in the preparation process of the metal hybridized magnetic nano-chitosan are screened, the proportions are adjusted, and the reaction conditions involved in the preparation steps are optimized. Specifically, the following are included: (1) screening of hybridized metal ions. Experimental results show that metal hybridized magnetic nano-chitosans of zirconium, lanthanum, cerium and aluminum ions all have good nucleic acid separation effects, but the nucleic acid separation performance of the magnetic nano-chitosan hybridized with lanthanum ions is the best. (2) the amount of SDS added in the activation reagent is adjusted. Experimental results show that among the amounts of SDS added of 0, 1 mmoL, 2.5 mmoL, 5 mmoL and 7.5 mmoL, the DNA adsorption capacity of the metal hybridized magnetic nano-chitosan prepared at 2.5 mmoL is the best. (3) the amount of hybridized metal salt added. Experimental results show that among the amounts of hybridized metal salt added of 1 mmoL, 2.5 mmoL, 5 mmoL and 10 mmoL, 5 mmoL has the best DNA adsorption capacity. The DNA adsorption capacity of metal hybridized magnetic nano-chitosan prepared by adding 200 mmoL hybrid metal salt is the best; (4) Optimization of metal hybridization reaction temperature. Experimental results show that the DNA adsorption capacity of metal hybridized magnetic nano-chitosan is the best when the metal hybridization reaction temperature is 60°C among the ranges of 50°C, 60°C, 70°C and 80°C.
[0036] In the preparation of the metal hybridized magnetic nano-chitosan nanoparticles of the present invention, the magnetic nano-ferroferric oxide is quickly synthesized, the material is added once and no gas protection device is required, which is convenient and quick; the silicon-based activation step is conducive to better bonding with chitosan; the metal hybridization modifies the surface of chitosan with nano hydroxide to increase the specific surface area and active adsorption sites of the material; the reagent conditions of each step interact synergistically to jointly affect the nucleic acid binding ability of the prepared metal hybridized magnetic nano-chitosan nanoparticles.
[0037] The extraction described in the present invention is to obtain a certain concentration of a target substance from a mixture. It is known to those skilled in the art that, under certain circumstances, extraction is equivalent to separation and purification and has the same meaning, and the present invention does not limit this.
[0038] The invention provides a composition, which comprises auxiliary materials and at least one of the metal hybridized magnetic nano-chitosan nano-particles of the invention and / or the metal hybridized magnetic nano-chitosan nano-particles prepared by the preparation method of the invention.
[0039] Furthermore, the auxiliary materials include solvents, detergents, buffers, stabilizers, antioxidants and / or preservatives, etc., which are not limited in the present invention.
[0040] The present invention provides a reagent combination, which includes a nucleic acid extraction reagent and at least one of the following A) to C):
[0041] A), the metal hybridized magnetic nano-chitosan nanoparticles of the present invention;
[0042] B), metal hybrid magnetic nano-chitosan nanoparticles prepared by the preparation method of the present invention;
[0043] C), the nucleic acid extraction reagent of the present invention.
[0044] Further, the nucleic acid extraction reagent includes at least one of a binding solution and / or an elution solution;
[0045] The present invention provides the use of at least one of the following I) to IV) in nucleic acid extraction:
[0046] I), the metal hybridized magnetic nano-chitosan nanoparticles of the present invention;
[0047] II), metal hybridized magnetic nano-chitosan nanoparticles prepared by the preparation method of the present invention;
[0048] III), the nucleic acid extraction reagent of the present invention;
[0049] IV), the reagent combination described in the present invention.
[0050] The present invention provides a method for extracting nucleic acid, which comprises extracting nucleic acid using at least one of the following i) to iv:
[0051] i), the metal hybridized magnetic nano-chitosan nanoparticles of the present invention;
[0052] ii), metal hybridized magnetic nano-chitosan nanoparticles prepared by the preparation method of the present invention;
[0053] iii), the nucleic acid extraction reagent of the present invention;
[0054] iv), the reagent combination described in the present invention.
[0055] Specifically, in the present invention, the method for extracting nucleic acid comprises the following steps: the sample reacts with a binding solution and magnetic nano-chitosan, followed by magnetic separation, and the nucleic acid is obtained by washing and eluting;
[0056] The binding solution is a mixed solution of polyethylene glycol and sodium chloride, wherein the polyethylene glycol has a molecular weight of 6000 and a mass fraction of 10-20%; the sodium chloride concentration is 4M, and the pH is 3-3.5;
[0057] The washing reagent is ethanol, specifically 80% ethanol;
[0058] The eluting reagent is pure water;
[0059] In the present invention, the nucleic acid includes DNA and RNA, which may be single-stranded or double-stranded, and the present invention is not limited thereto. In a specific embodiment of the present invention, the nucleic acid is DNA;
[0060] The sample described in the present invention is a sample containing nucleic acid, which can be water, buffer, cell fluid, and / or tissue fluid, etc., and the present invention is not limited to this.
[0061] The invention provides metal hybridized magnetic nano chitosan nanoparticles with high DNA adsorption performance. Compared with the prior art, the preparation steps are simple and rapid, the rapid and high-throughput separation of nucleic acids can be achieved, and the particles can be reused, thus having wide application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 The preparation process of metal hybrid magnetic nano-chitosan is shown;
[0063] Figure 2 Shows the size distribution of metal hybridized magnetic nano-chitosan;
[0064] Figure 3 Shows the BET isotherm of metal hybridized magnetic nano-chitosan;
[0065] Figure 4 The magnetic responsiveness of metal hybrid magnetic nano-chitosan is shown;
[0066] Figure 5 The results show the DNA separation effect of metal hybrid magnetic nano-chitosan;
[0067] Figure 6 The adsorption efficiency of metal hybrid magnetic nano-chitosan is shown;
[0068] Figure 7 The reusability of metal hybrid magnetic nano-chitosan is shown;
[0069] Figure 8 The results show the comparison of the effects of different metal hybridization types on DNA extraction and separation;
[0070] Fig. 9 The optimization of the amount of SDS added in the preparation of metal hybrid magnetic nano-chitosan is shown;
[0071] Fig.10 The optimization of metal hybridization reaction temperature in the preparation of metal hybridized magnetic nano-chitosan is shown;
[0072] Fig.11 The optimization of the amount of hybrid metal salt added in the preparation of metal hybrid magnetic nano-chitosan is shown;
[0073] Fig.12The figure shows the comparison between the metal hybridized magnetic nano-chitosan prepared by the present invention and the prior art. DETAILED DESCRIPTION
[0074] The present invention provides metal hybridized magnetic nano-chitosan and its application. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described by preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0075] The present invention provides a method for extracting nucleic acid based on metal hybridized magnetic nano-chitosan from the perspective of economy, safety and biocompatibility, thereby obtaining a high-throughput rapid DNA separation technology. The present invention utilizes the cationicity and biocompatibility of chitosan and its ability to bind to DNA, and through further metal hybridization modification, significantly increases the specific surface area and active adsorption sites of the material, thereby significantly improving the DNA capture ability.
[0076] The test materials used in the present invention are all common commercial products and can be purchased on the market. The present invention is further described below in conjunction with the embodiments:
[0077] Example 1 Preparation and application of core-shell metal hybrid magnetic nano-chitosan
[0078] 1. Preparation and performance determination of core-shell metal hybrid magnetic nano-chitosan
[0079] 1. The preparation process of core-shell metal hybrid magnetic nano-chitosan is as follows Figure 1 As shown, the specific preparation method is as follows:
[0080] (1) Preparation of magnetic nanoparticles
[0081] Dissolve 0.01 mol ferrous sulfate and 0.03 mol ferric chloride in 50 mL water, then immediately pour into 100 mL 4M preheated sodium hydroxide solution (temperature 60-65°C), mechanically stir (400-800 rpm) for 1.5 h, then magnetically separate, wash with pure water until neutral, freeze-dry, and obtain magnetic nanoparticles for later use.
[0082] (2) Silica modification and activation of magnetic nanoparticles
[0083] Weigh 80 mL of anhydrous ethanol into a 250 mL flask, add 1 g of magnetic nanoparticles, and sonicate for 20 min. Then, add a mechanical stirrer, add 16 mL of water and 2 mL of ammonia water, slowly add 2 mL of tetraethyl orthosilicate, stir the mixture at room temperature for 12 h, and finally separate it by magnetic separation, wash it with ethanol and water alternately 3 times, and separate the solid by magnetic separation. The solid product was redispersed in 100 mL of water, 2.9 g of sodium chloride and 0.72 g of SDS (sodium dodecyl sulfate, molecular weight 288.38, about 2.5 mmoL) were added, stirred at room temperature for 4 h, separated by magnetic separation, washed with pure water 3 times, and vacuum dried for 24 h to obtain activated silica-modified magnetic nanoparticles.
[0084] (3) Preparation of magnetic nano-chitosan
[0085] Weigh 50 mL of acetic acid buffer (pH 3.6), add 1 g of chitosan (deacetylation degree > 95%, molecular weight 50,000), stir and dissolve, then add the product from the previous step, stir at room temperature for 12 h, perform magnetic separation, wash once with 1% acetic acid, wash twice with pure water, and vacuum dry for 24 h to obtain magnetic nano-chitosan.
[0086] (4) Metal hybridization treatment
[0087] Take 1.5g of magnetic nano-chitosan and disperse it in 100mL of 10% ethanol, add 5mmol of metal salt (lanthanum nitrate), ultrasonicate for 15min, stir at room temperature for 2h, heat to 60℃ (metal hybridization reaction temperature), slowly add 10mL of sodium hydroxide solution (1.5~2M), after the addition is complete, react for another 2h, then stop heating, continue stirring at room temperature for 24h, magnetically separate, wash, and vacuum dry to obtain metal hybridized magnetic nano-chitosan.
[0088] 2. Performance determination of core-shell metal hybrid magnetic nano-chitosan
[0089] The particle size, isothermal spectrum and magnetic responsiveness of metal hybrid magnetic nano-chitosan were measured. Figure 2 , Figure 3 and Figure 4 As shown, Figure 2 , Figure 3 nuclear Figure 4 In the process, the raw metal salt will react to form a hydroxide, wherein lanthanum nitrate is added to form lanthanum hydroxide. Figure 2 It shows that the particle size of metal hybridized magnetic nano-chitosan is mainly concentrated around 100 nm and the distribution is relatively uniform; Figure 3 It shows that the specific surface area of magnetic nano-chitosan increased by about 1.4 times after metal (lanthanum hydroxide) hybridization, which increased the adsorption sites; Figure 4 It shows that metal hybrid magnetic nano-chitosan has good superparamagnetism.
[0090] 2. Metal-hybridized magnetic nano-chitosan nucleic acid separation method and nucleic acid separation results
[0091] 1. Metal hybrid magnetic nano-chitosan nucleic acid separation method
[0092] (1) Take 500 μL of sample solution containing free DNA (any solution containing free DNA can be extracted, including water, buffer, cell fluid, tissue fluid, and has a wide range of applications. The sample solution at this time is water) and place it in a centrifuge tube. Add 500 μL of binding solution and 10 mg of metal hybridized magnetic nano-chitosan. Vortex and mix well. Invert and mix once every minute. Keep for 5 to 10 minutes to allow the magnetic beads to fully bind to the DNA.
[0093] (2) Place the centrifuge tube on a magnetic rack for 2 min, remove the liquid with a pipette, add 1 mL of 80% ethanol, mix by inverting to fully suspend the magnetic beads, remove the sample liquid remaining on the surface, place on a magnetic rack to remove the ethanol, and dry at room temperature for 10-15 min to allow the ethanol to fully evaporate;
[0094] (3) Add 200 μL of elution buffer and incubate at 70°C for 20 min. Finally, place the centrifuge tube on a magnetic rack for separation. The extracted DNA solution is stored in a -20°C environment.
[0095] Binding solution: a mixed solution of polyethylene glycol and sodium chloride. The molecular weight of polyethylene glycol is 6000, and the mass fraction is 10-20%; the concentration of sodium chloride is 4 M, and the pH is 3-3.5.
[0096] Eluent: water, adjusted to pH 10.5;
[0097] 2. Separation results of nucleic acid by metal hybrid magnetic nano-chitosan
[0098] Metal hybrid magnetic nano-chitosan DNA separation effect Figure 5 As shown, the DNA adsorption capacity of magnetic nano-chitosan after metal hybridization can reach 300-500 mg / g, which is significantly higher than the existing products on the market. The DNA separation magnetic beads on sale have a loading capacity of about 10-200 mg / g.
[0099] The adsorption efficiency of metal hybrid magnetic nano-chitosan is as follows Figure 6 As shown, after metal hybridization, magnetic nano-chitosan can reach an adsorption capacity of more than 90% in about 10 minutes, which significantly improves the separation efficiency;
[0100] The reusability of metal hybrid magnetic nano-chitosan Figure 7As shown in the figure, after repeated adsorption-desorption cycles, the separation capacity can still be maintained at more than 90% after being reused for 5 times.
[0101] Example 2 Optimization of the hybrid metal of the present invention and comparison with the prior art
[0102] 1. Optimization of metal hybrid magnetic nano-chitosan
[0103] Except for the following screening targets which are different from those in Example 1, other parameter characteristics remain the same as those in Example 1.
[0104] (1) Screening and optimization of hybrid metals
[0105] The results of nucleic acid separation of magnetic nano-chitosan hybridized with different metals were shown in Figure 2. Figure 8 As shown, zirconium, lanthanum, cerium and aluminum all have good separation effects, among which lanthanum is the best, followed by zirconium, and then metallic cerium. Their nucleic acid separation abilities are significantly better than metallic aluminum.
[0106] (2) Optimization of the amount of SDS added
[0107] The optimization results are as follows Fig. 9 As shown, the amount of SDS added was set to 0, 1 mmoL, 2.5 mmoL, 5 mmoL, and 7.5 mmoL, among which the DNA adsorption capacity of the metal hybridized magnetic nano-chitosan was optimal when the amount of SDS added was 2.5 mmoL.
[0108] (3) Optimization of metal hybridization reaction temperature
[0109] The optimization results are as follows Fig.10 As shown, the metal hybridization reaction temperature is set to 50°C, 60°C, 70°C and 80°C, among which the DNA adsorption capacity of the metal hybridized magnetic nano-chitosan is optimal when the metal hybridization reaction temperature is 60°C.
[0110] (4) Optimization of the amount of hybrid metal salt added
[0111] The optimization results are as follows Fig.11 As shown, the addition amount of the hybrid metal salt was set to 1 mmoL, 2.5 mmoL, 5 mmoL and 10 mmoL, among which the DNA adsorption capacity of the metal hybrid magnetic nano-chitosan was optimal when the addition amount of the hybrid metal salt was 5 mmoL.
[0112] 2. Comparison of existing technologies
[0113] 1. The results are as follows Fig.12As shown, A and C are the effects of the magnetic nano-chitosan and metal-hybridized magnetic nano-chitosan prepared in this scheme on DNA extraction and separation, wherein A is the magnetic nano-chitosan obtained through steps (1) to (3) of Example 1 without metal hybridization treatment; C is the magnetic nano-chitosan hybridized with lanthanum ions; B and D are beads or microspheres prepared by the prior art, B is the beads or microspheres prepared by 202210766714.8 and D is the beads or microspheres prepared by 201810455942.7. It can be found that the prior art is far from achieving the effect and performance of this scheme, and there are significant differences in structure, performance and stability.
[0114] 2. Regarding the preparation method of magnetic chitosan, the Chinese invention patent application No. 202210766714.8 discloses a method for preparing magnetic chitosan gel beads, which are used in the field of water treatment. This scheme adopts a cross-linking method to prepare chitosan into gel beads and incorporates magnetic particles. The size, structure and performance of the gel beads prepared by this scheme are uncontrollable, and are only applicable to a relatively stable and broad water treatment field.
[0115] At the same time, China's invention patent application No. 201810455942.7 discloses a lanthanum-loaded chitosan magnetic microsphere composite and its preparation method and application. The preparation method of this scheme also adopts the method of mixing the raw materials and dripping them into alkaline solution. This scheme can only prepare micron-level composites, and lanthanum is loaded in the internal pores of the microspheres. Although this porous structure helps to adsorb a large amount of pollutants, the pollutants are difficult to separate from the inside of the microspheres, and cannot meet the performance requirements of separation, purification and recycling.
[0116] This scheme prepares magnetic chitosan nanoparticles with a multilayer core-shell structure, and uses metal hybridization technology to prepare high-performance metal hybrid magnetic nano-chitosan for nucleic acid extraction. The nanoparticles prepared by this scheme have controllable structure, good uniformity and stability, high extraction efficiency, large nucleic acid loading capacity, and strong reusability. Its performance far exceeds the existing technical schemes. The preparation process of this scheme is different from the existing technical schemes. This scheme does not require high temperature and high pressure treatment or inert gas protection. The silicon-based group is activated by sodium dodecyl sulfate and a multi-branch structure is added to significantly improve the surface performance. The structure size is controllable, and a high-efficiency and high-performance nucleic acid extraction and separation method is obtained through hybridization technology modification.
[0117] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Metal hybridized magnetic nano-chitosan nanoparticles, characterized in that: The invention comprises magnetic ferroferric oxide nanoparticles, silicon dioxide, sodium dodecyl sulfate, chitosan and metal ions.
2. The metal hybridized magnetic nano-chitosan nanoparticles according to claim 1, characterized in that: The metal ions are selected from at least one of lanthanum, cerium, zirconium and / or aluminum ions.
3. The metal hybridized magnetic nano-chitosan nanoparticles according to claim 1 or 2, characterized in that: The metal hybridized magnetic nano-chitosan nanoparticles include: Magnetic Fe3O4 nanoparticles; Silicon dioxide covering the magnetic ferroferric oxide nanoparticles; Sodium lauryl sulfate coated on the silicon dioxide; Chitosan coated on the sodium dodecyl sulfate; and metal ions doped in the chitosan; The particle size of the metal hybrid magnetic nano-chitosan nanoparticles is 60-140 nm.
4. The method for preparing the metal hybridized magnetic nano-chitosan nanoparticles according to any one of claims 1 to 3, characterized in that: The steps include: Step 1, the magnetic ferroferric oxide nanoparticles are modified by silica to obtain silica-modified magnetic ferroferric oxide nanoparticles, and the silica-modified magnetic ferroferric oxide nanoparticles are activated by sodium dodecyl sulfate to obtain activated silica-modified magnetic nanoparticles; Step 2, the activated silica modified magnetic nanoparticles are coated with chitosan to obtain magnetic nano-chitosan; Step 3: The magnetic nano-chitosan is hybridized with metal ions to obtain the metal-hybridized magnetic nano-chitosan nanoparticles.
5. The preparation method according to claim 4, characterized in that: In step 1, the mass ratio of the silica-modified magnetic nanoparticles to sodium dodecyl sulfate is 1:(0.5-1.2).
6. The preparation method according to claim 4, characterized in that: In step 2, the mass ratio of activated silica modified magnetic nanoparticles to chitosan is 1:(0.5~2).
7. The preparation method according to claim 4, characterized in that: In step 3, the mass ratio of the magnetic nano-chitosan to the metal salt containing the metal ion is 1:(0.5-2).
8. A composition, characterized in that The invention comprises at least one of the metal hybridized magnetic nano-chitosan nanoparticles according to any one of claims 1 to 3 and / or the metal hybridized magnetic nano-chitosan nanoparticles prepared by the preparation method according to any one of claims 4 to 8 and auxiliary materials.
9. A reagent combination, characterized in that It includes a nucleic acid extraction reagent and at least one of the following A) to C): A), the metal hybrid magnetic nano-chitosan nanoparticles according to any one of claims 1 to 3; B), metal hybrid magnetic nano-chitosan nanoparticles prepared by the preparation method according to any one of claims 4 to 7; C) The nucleic acid extraction reagent according to claim 8.
10. Application of at least one of the following I) to IV) in nucleic acid extraction: I), the metal hybridized magnetic nano-chitosan nanoparticles according to any one of claims 1 to 3; II), metal hybrid magnetic nano-chitosan nanoparticles prepared by the preparation method according to any one of claims 4 to 7; III), the nucleic acid extraction reagent according to claim 8; IV), the reagent combination according to claim 9.
